Association between dietary mineral intake and new onset diabetes/pre-diabetes after chronic pancreatitis - Li, Bingqing; Guo, Shan; Zong, Wenlu; Chu, Yuning; Zhang, Qi; Yin, Xiaoyan; Mao, Tao; Li, Xiaoyu (Frontiers in Nutrition, 2025)
Background and aimsAs the main type of pancreatic diabetes, patients with new diabetes after chronic pancreatitis are often difficult to manage and have poor prognosis. This study aimed to figure out the association between dietary mineral intake and glucose metabolism with chronic pancreatitis.MethodThe study included 114 patients with chronic pancreatitis, who were grouped based on the sequence of onset for chronic pancreatitis and diabetes: normoglycaemia after chronic pancreatitis (NCP), type 2 diabetes (T2DM), and new-onset diabetes or pre-diabetes after chronic pancreatitis (NODCP). The habitual intake of 10 minerals (calcium, chlorine, iodine, iron, magnesium, phosphorus, potassium, selenium, sodium, and zinc) was assessed using a dietary health questionnaire. The differences in mineral intake between the groups were compared, and the relationship between mineral intake and key glucose metabolism markers, including fasting plasma glucose (FPG), glycated hemoglobin (HbA1c), and fasting insulin, was analyzed using regression models.ResultsCompared with normal glycaemic status after chronic pancreatitis, the intake of iron and phosphorus in patients with new diabetes/pre-diabetes after chronic pancreatitis (NODCP) has changed significantly. In the NODCP group, FPG levels were significantly negatively correlated with magnesium intake, while HbA1c levels were significantly negatively correlated with average phosphorus intake. In addition, there is a correlation between fasting insulin and average magnesium intake in the NODCP group. No correlation was found between the intake of other minerals and glucose metabolism in chronic pancreatitis.ConclusionThe intake of minerals in the diet affects the glycaemic status after chronic pancreatitis. It is necessary to further explore the possible causal relationship and mechanism between mineral intake and diabetes after chronic pancreatitis, so as to provide evidence for nutritional intervention of high-risk patients.